The War on Public Education: Agonist Democracy and the Fight for Schools as Public Things - Knight Abowitz, Kathleen (Philosophical Inquiry in Education, 2018)
Agonistic critiques of democratic theory conceptualize democracy as a site of conflict and struggle; as the fight against privatization escalates, these critiques become more relevant for educational governance. Public education governance has, in addition, increasingly been the site of growing conflicts between federal, states and local levels, as populist and other types of dissent are now emerging in educational politics. These conflicts reached a new nexus with the nomination of Betsy DeVos as U.S. Secretary of Education. This nomination represents a vivid battle over public school as a “public thing,” a material object, space, institution or place of symbolic and embodied civic importance (Honig 2017). DeVos’ nomination stirred up, in popular imagination, the idea of public schools as “public things” of meaning and value for many citizens who participated in unprecedented ways to (unsuccessfully) block her appointment. It was with this threat to public education that the value of school as a “public thing” became crystalized among a diverse network of citizens. This political moment reveals 1) the nature of schools as public things, 2) the importance of agonist critiques of democracy, and public work, as a means for citizens to help safe-guard the future of schools as public things. I conclude by explaining the limits of agonism as a comprehensive approach to the democratic governance of schooling, advocating for its use as a critique and expansion of current models of public engagement with educational politics.